MANAJEMEN KRISIS BANK MANDIRI DALAM MENJAGA REPUTASI PERUSAHAAN: Studi Kasus Perubahan Saldo Rekening Sebagian Nasabah Bank Mandiri pada 20 Juli 2019 - Nisa Auliya Rachmasari, (2020)
The role of public relations in a company has various responsibilities in terms of corporate communication. Therefore if the company experiences a problem or crisis then public relations must be able to handle the crisis so it will not affect the company's reputation. On 20 July 2019, Bank Mandiri was faced with a crisis related to the company's reputation. Starting with customer complaints on Bank Mandiri social media and Bank Mandiri customer care, complants that have been submitted by customers is the nominal balance on their accounts has changes, that have caused news to various media related to this case. In this case the reputation risk management team, which is the duty of the Corporate Secretary, plays a role in handling the crisis through communication actions. Press conferences and press releases become one of the public relations tools used by Corporate Secretary Bank Mandiri in carrying out its communication strategy. The method used in this study is qualitative methods with a case study approach. The purpose of this study was to know about the manaegement crisis actions of public relations taken by Bank. The results of this study are the Corporate Secretary of Bank Mandiri, which acts as a corporate crisis management quickly respond to customer complaints and media reports and immediately gather the informations that are related to the crisis and decide on communication actions. Press conferences that are broadcast on almost all private tv are able to reach various levels of society simultaneously. The contents of the message in the press conference are packaged as good as possible so society are easy to understand and press conferences are able to explain the situation so that the high level of public concern can decrease. Keywords: public relations, crisis management